2016
DOI: 10.1177/0956462416662379
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of quality of life in people living with HIV in Georgia

Abstract: The purpose of our study was to assess quality of life (QoL) among Georgian HIV-infected individuals and to examine factors associated with QoL. Our cross-sectional study sample consisted of 201 HIV-infected adult outpatients recruited at the National AIDS Center in Tbilisi, Georgia. WHOQOL-HIV-BREF was used to measure QoL. Data about other variables of interest were obtained from medical records. Modified Poisson regression with robust variance estimates was performed to create a predictive model of factors t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
23
0
15

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 14 publications
11
23
0
15
Order By: Relevance
“…The lowest healthrelated quality of life was documented for the physical domain of QoL. In contrary to this finding, several studies reported better physical health-related QoL in Ethiopia [26] and other regions [18,20,27]. The possible explanation for this finding is that the participants were symptomatic and burdened with physical symptoms of the disease, which in turn, impairs HRQoL [28].…”
Section: Discussionmentioning
confidence: 92%
“…The lowest healthrelated quality of life was documented for the physical domain of QoL. In contrary to this finding, several studies reported better physical health-related QoL in Ethiopia [26] and other regions [18,20,27]. The possible explanation for this finding is that the participants were symptomatic and burdened with physical symptoms of the disease, which in turn, impairs HRQoL [28].…”
Section: Discussionmentioning
confidence: 92%
“…Karkashadze et al and Bakiono et al also noted that majority of patients were asymptomatic at the time of study which is quite similar to our study. 12,13 In our study, more than half (58.1%) patients had the disease due to sexual route of transmission while 38.1% patients don't know their mode of transmission. It is likely that they were unaware of the mode of transmission because of low literacy and lack of knowledge about the different routes of transmission of HIV.…”
Section: Discussionmentioning
confidence: 58%
“…Se describe menor score de CVRS asociado a menor nivel de escolaridad (3)(4)(5)(6)(7)(8)(9) , depresión/ansiedad (3,6,(9)(10)(11)(12)(13)(14)(15)(16) , preocupación financiera, falta de soporte económico o social (6,9,10,11,(17)(18)(19)(20)(21)(22) , presencia de síntomas (14,(21)(22)(23) , estigma o preocupación por la confidencialidad (12,17,23,24) , consumo de drogas y alcohol (4,5) , comorbilidades (4,5,25) , bajo nivel de confianza o pobre relacionamiento con el staff médico y menor accesibilidad al sistema de salud (11,17,25) .…”
Section: Introductionunclassified
“…El espectro va desde peor score en CVRS en personas con bajo recuento de CD4 (6,22,26,33) y mayor score entre aquellos con mejor inmunidad (4,31) , hasta aquellos que no encuentran asociación (5,10,11,19,22,34) . Son escasas las evidencias que muestran asociación de la CV indetectable con mejoría (34) o peoría (5) con el score de CVRS.…”
Section: Introductionunclassified
See 1 more Smart Citation